Characterization of a blaNDM-1-Bearing IncHI5-Like Plasmid From Klebsiella pneumoniae of Infant Origin - Liu, Ziyi; Chen, Ruifei; Xu, Poshi; Wang, Zhiqiang; Li, Ruichao (Frontiers in Cellular and Infection Microbiology, 2021)
The spread of plasmid-mediated carbapenem-resistant clinical isolates is a serious threat to global health. In this study, an emerging NDM-encoding IncHI5-like plasmid from Klebsiella pneumoniae of infant patient origin was characterized, and the plasmid was compared to the available IncHI5-like plasmids to better understand the genetic composition and evolution of this emerging plasmid. Clinical isolate C39 was identified as K. pneumoniae and belonged to ST37 and KL15 serotype. Whole genome sequencing (WGS) and analysis revealed that it harbored two plasmids, one of which was a large IncHI5-like plasmid pC39-334kb encoding a wide variety of antimicrobial resistance genes clustered in a single multidrug resistance (MDR) region. The blaNDM-1 gene was located on ΔISAba125-blaNDM-1-bleMBL-trpF-dsbC structure. Comparative genomic analysis showed that it shared a similar backbone with four IncHI5-like plasmids and the IncHI5 plasmid pNDM-1-EC12, and these six plasmids differed from typical IncHI5 plasmids. The replication genes of IncHI5-like plasmids shared 97.06% (repHI5B) and 97.99% (repFIB-like) nucleotide identity with those of IncHI5 plasmids. Given that pNDM-1-EC12 and all IncHI5-like plasmids are closely related genetically, the occurrence of IncHI5-like plasmid is likely associated with the mutation of the replication genes of pNDM-1-EC12-like IncHI5 plasmids. All available IncHI5-like plasmids harbored 262 core genes encoding replication and maintenance functions and carried distinct MDR regions. Furthermore, 80% of them (4/5) were found in K. pneumoniae from Chinese nosocomial settings. To conclude, this study expands our knowledge of the evolution history of IncHI5-like plasmids, and more attention should be paid to track the evolution pathway of them among clinical, animal and environmental settings.